Anaerobic degradation of cyclohexane by sulfate-reducing bacteria from hydrocarbon-contaminated marine sediments - Jaekel, Ulrike; Zedelius, Johannes; Wilkes, Heinz; Musat, Florin (Frontiers in Microbiology, 2015)
The fate of cyclohexane, often used as a model compound for the biodegradation of cyclic alkanes due to its abundance in crude oils, in anoxic marine sediments has been poorly investigated. In the present study, we obtained an enrichment culture of cyclohexane-degrading sulfate-reducing bacteria from hydrocarbon-contaminated intertidal marine sediments. Microscopic analyses showed an apparent dominance by oval cells of 1.5×0.8 m. Analysis of a 16S rRNA gene library, followed by whole-cell hybridization with group- and sequence-specific oligonucleotide probes showed that these cells belonged to a single phylotype, and were accounting for more than 80% of the total cell number. The dominant phylotype, affiliated with the Desulfosarcina-Desulfococcus cluster of the Deltaproteobacteria, is proposed to be responsible for the degradation of cyclohexane. Quantitative growth experiments showed that cyclohexane degradation was coupled with the stoichiometric reduction of sulfate to sulfide. Substrate response tests corroborated with hybridization with a sequence-specific oligonucleotide probe suggested that the dominant phylotype apparently was able to degrade other cyclic and n-alkanes, including the gaseous alkanes propane and n-butane. Based on GC-MS analyses of culture extracts cyclohexylsuccinate was identified as a metabolite, indicating an activation of cyclohexane by addition to fumarate. Other metabolites detected were 3-cyclohexylpropionate and cyclohexanecarboxylate providing evidence that the overall degradation pathway of cyclohexane under anoxic conditions is analogous to that of n-alkanes.